Real time implementation and validation of lean implementation model for sustainability (LIMS) in medium scale industry - Gunasekharan, S; Elangovan, D; Sudhakara Reddy, S; Maheswari, M (International Journal of Engineering and Technology, 2018)
Lean manufacturing is a strategic tool, which is used to cut down waste and to improve the efficiency of an organization and helps the organization to sustain in the competitive environment. Implementation of lean systems in organization results in reduce energy consumption, waste generation, and hazardous materials used while also building the companies’ images as socially responsible organizations. Several research efforts discussed in the literature indicate that lean companies show significant environmental improvements by being more resource and energy efficient. Lean systems are associated with waste reduction techniques. In foreign, many industries have started implementing these concepts and they are getting good results. In India, companies are facing problems in implementing lean concept. Critical success factors for lean system implementation in Indian medium scale manufacturing industries has been identified to overcome it. The factors are grouped into different levels by Interpretive Structural Modelling (ISM). A lean implementation model has been developed for medium scale industry and named as ’LIMS’. This paper investigates the implementation and validation of the LIMS through the real time implementation in a medium scale industry.